Pendampingan Penyusunan Peraturan Desa Bagi Anggota Badan Permusyawaratan Desa Se-Kecamatan Sejangkung Kabupaten Sambas - Syamsiah, Nur; Beti Yanuri Posha (Lembaga Pengembangan Kinerja Dosen, 2025)
This article is a community service report on assistance in drafting village regulations for members of the Village Consultative Body (BPD) throughout Sejangkung Subdistrict, Sambas Regency. Based on field observations, it was found that no BPD had yet demonstrated the capability to propose and draft village regulations jointly with the village head. This study aims to optimize one of the main duties and functions of the BPD, namely to discuss and approve Draft Village Regulations in collaboration with the village head. The implementation method included organizing activities such as:Preparation, which involved preparing correspondence, providing materials/content, and media for delivering the material;Activity Execution, which began with an opening session, presentation on the stages of drafting village regulations, identification of subjects or themes that require regulation, and assistance in drafting the proposed village regulations.The results of this activity showed an increase in knowledge among all BPD members in Sejangkung Subdistrict regarding the drafting and discussion of village regulations. In addition, one village succeeded in producing a finalized village regulation.